The effects of quantifier size on the construction of discourse models. (August 2022) - Klingvall, Eva; Heinat, Fredrik
Abstract: Sentences with quantified expressions involve mental representations of sets of individuals for which some property holds (the reference set), as well as of sets for which the property does not hold (the complement set). Both sets can receive discourse focus with negative quantifiers, while the reference set is strongly preferred with positive quantifiers, complement set focus however being possible if contextually motivated. In an offline semantic plausibility study and two online EEG studies, we investigated whether the complement set is an available discourse entity inherently for positive quantifiers, as it is for negative quantifiers. The results show that while the default focus patterns induced by positive and negative quantifiers are robust, both complement and reference set are represented as discourse entities and this is to our knowledge the first study to show that even positive quantifiers make both reference and complement set mentally represented during discourse processing without contextual influence. We also discuss the impact the results from the two ERP studies have on the functional interpretation of two well known ERP effects: the N400 and the P600. Highlights: The proportion between the Reference set (for which some property is true) and the Complement set (for which the property is not true) of quantifiers matters in both offline acceptability and online processing. Proportionally larger sets are preferred over smaller sets and induce less processing difficulty. Not only negative quantifiers, but also positive ones make both the Reference set and the Complement set mentally represented during discourse processing, without contextual influence. The results support an approach where the N400 effect is related to lexical retrieval and the P600 effect is related to discourse integration.